Effect of turning vs. supine position under phototherapy on neonates with hyperbilirubinemia: a systematic review - Lee, Shalin Wan Fei; Khatijah Lim, Abdullah (John Wiley & Sons Ltd, 2015)
Aims and objectives. To determine the most effective position jaundiced neonates should assume during phototherapy from appraised randomised controlled trials. Background. Many local hospitals still alternate positions of jaundiced neonates receiving phototherapy despite the safe infant sleeping protocol of placing them supine. Design. A systematic review was conducted. Methods. Databases that included Cumulative Index to Nursing and Allied Health Literature, ScienceDirect, Embase and The Cochrane Library were used. Randomized controlled trials published in English language that evaluate the best position for healthy jaundiced neonates aged day 1 to 14 under phototherapy were searched. In addition, any positioning done every 2–3 hours during phototherapy with the outcome measures being bilirubin reduction and duration of phototherapy were also searched and included (n = 5). Physiotherapy Evidence Database scale was adopted for quality assessment. All processes were conducted by both reviewers independently. Discrepancies were resolved by a third reviewer. Preferred Reporting Items for Systematic Reviews and Meta-Analyses Guideline were utilised. Out of 20 papers, five were included for qualitative synthesis. Data extraction was based on the template (participants, study designs etcetera) agreed by both authors. Results. All five studies possessed external validity. One paper scored 7, three scored 5 while one scored 3. Four of these studies reported no difference in bilirubin reduction and duration of phototherapy. Only one study reported a significant drop in serum bilirubin and shorter duration of phototherapy in the supine group. Conclusion. It has been proved that keeping the jaundiced newborns in the supine position throughout phototherapy is as effective as turning them periodically based on the appraised studies.